Aluminum alloy brazing sheet and its manufacturing method

The aluminum alloy brazing sheet with controlled oxide-forming elements addresses the challenge of fluxless bonding in aluminum products, achieving effective brazing in inert gas atmospheres by exposing a new surface during heat, thus improving joint integrity and reducing costs.

JP7603002B2Active Publication Date: 2024-12-19UACJ CORP
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2021512323
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-04-04
Filing Date
2020-04-03
Publication Date
2024-12-19
Estimated Expiration
2040-04-03

AI Technical Summary

Technical Problem

Existing brazing methods for aluminum products face challenges in achieving effective bonding without using flux, particularly in joints with large gaps, due to the high costs and maintenance issues associated with flux use, and the formation of distorted fillets or insufficient brazing properties in vacuum heating processes.

Method used

An aluminum alloy brazing sheet is developed with specific compositions for the core and brazing filler metals, incorporating elements like Mg, Li, and Ca to form oxides with a controlled volume change rate, allowing for effective bonding in an inert gas atmosphere without flux, and a manufacturing process involving controlled annealing and etching to manage oxide films.

Benefits of technology

The solution provides excellent brazing properties in inert gas atmospheres, ensuring effective bonding even in joints with large gaps, without the need for flux, by exposing a new surface during brazing heat through controlled oxide formation, thereby enhancing joint integrity and reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007603002000005
    Figure 0007603002000005
  • Figure 0007603002000001
    Figure 0007603002000001
  • Figure 0007603002000002
    Figure 0007603002000002
Patent Text Reader

Abstract

Provided is an aluminum alloy brazing sheet used for brazing in an inert gas atmosphere without using a flux, wherein a brazing material is clad on at least one surface of the core of the aluminum alloy brazing sheet, and an oxide containing one or at least two among Mg, Li, and Ca is formed on the surface of the aluminum alloy brazing sheet by brazing heating, with a volume change of 0.990 or less with respect to a surface oxide film prior to brazing heating. The aluminum alloy brazing sheet is characterized in that the atomic molar ratio of Mg, Li, and Ca to Al in oxides formed on the surface of the aluminum alloy brazing sheet prior to brazing heating is 0.50 or less. According to the present invention, an aluminum alloy brazing sheet having excellent brazing properties for brazing in an inert gas atmosphere without using a flux, and a method for manufacturing same can be provided.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an aluminum alloy brazing sheet used for brazing aluminum or an aluminum alloy in an inert gas atmosphere without using a flux, and a method for producing the same. [Background technology]

[0002] Brazing is widely used as a method for joining aluminum products that have many fine joints, such as aluminum heat exchangers and machine parts. To braze aluminum or aluminum alloys, the oxide film covering the surface is destroyed to expose the molten brazing material, and the base material or the molten brazing material is wetted with the brazing material. Give rise to It is essential to destroy the oxide film, and there are two main methods for destroying the oxide film: a method using a flux in a nitrogen gas furnace, and a method not using a flux in a vacuum heating furnace. Both methods are in practical use.

[0003] In the method using flux in a nitrogen gas furnace, the flux reacts with the oxide film during brazing heating, destroying it. However, there are problems with the cost of the flux and the cost of the process of applying the flux. In addition, if the flux is applied unevenly, there is a risk of brazing defects. On the other hand, in the method not using flux in a vacuum heating furnace, a brazing filler metal made of an Al-Si-Mg alloy is used, and the Mg in the brazing filler metal is destroyed by heating in a vacuum. but The magnesium vaporizes and destroys the oxide film on the surface of the material. However, it has the disadvantage of requiring expensive vacuum heating equipment. In addition, the evaporated magnesium adheres to the inside of the furnace, and the maintenance costs for removing the adhered magnesium are high. Therefore, there is a growing need for joining in a nitrogen gas furnace without using flux.

[0004] In order to meet such needs, for example, Patent Document 1 proposes that by including Mg in the brazing material, surface joining becomes possible. In addition, Patent Document 2 proposes that by including Mg in the core material and diffusing Mg into the brazing material during brazing heating, fillet formation becomes possible in a simple fin / tube joint. Furthermore, Patent Document 2 discloses that good flux-free brazing properties can be obtained by limiting the circle equivalent diameter and number of Si particles contained in the brazing material and by bringing the brazing material and the brazing material into contact and tightly adhering. However, in these methods, in joints with gaps, sufficient fillets cannot be formed without applying flux. That is, in these methods, the oxide film is broken into particles by Mg, and then the new surface of the molten brazing material is exposed by the thermal expansion difference between the molten brazing material and the oxide film or an external force such as the flow of the brazing material, causing wetting. For this reason, these methods form distorted fillets accompanied by fillet breakage.

[0005] Also, Patent Document 3 proposes that it is effective to suppress the thickness of the MgO film present on the oxide film before brazing heat. However, in Patent Document 3, in which the brazing material contains 0.1 mass% or more of Mg, in practical joints, an MgO-based film is partially formed during brazing heat, which inhibits the formation of a fillet and causes fillet breakage. On the other hand, Patent Document 4 proposes a method in which, in a material containing 0.05 mass% or more of Mg in the brazing material, an acid pickling treatment is performed before brazing heat to remove the MgO-based film, thereby enabling fluxless brazing. However, as in Patent Document 1, the formation of the MgO-based film during brazing heat cannot be sufficiently suppressed.

[0006] Therefore, Patent Document 5 proposes a brazing sheet on the surface of which oxide particles containing an X element (X is Mg, Li, Be, Ca, Ce, La, Y, or Zr) are formed, the volume change rate of which is 0.99 or less relative to the oxide film before brazing heat. This improves the brazeability for practical joints with gaps, but the gaps in actual heat exchangers are larger, so the brazeability may not be sufficient. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2013-215797 A [Patent Document 2] Patent No. 4547032 [Patent Document 3] JP 2004-358519 A [Patent Document 4] Japanese Patent Application Publication No. 11-285817 [Patent Document 5] JP 2017-074609 A DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]

[0008] An object of the present invention is to provide an aluminum alloy brazing sheet and a manufacturing method thereof, which have excellent brazing properties not only in the contact and adhesion parts between the components of a heat exchanger but also when there are large gaps, when brazing in an inert gas atmosphere without using flux. [Means for solving the problem]

[0009] The above problems can be solved by the present invention described below. That is, the present invention (1) is an aluminum alloy brazing sheet used for brazing in an inert gas atmosphere without using a flux, At least one side of the core material is clad with a brazing material; the core material is an aluminum alloy core material containing aluminum or one or more of 1.50 mass% or less Fe, 1.50 mass% or less Si, 2.00 mass% or less Cu, 2.00 mass% or less Mn, 3.00 mass% or less Zn, 0.30 mass% or less Cr, 0.30 mass% or less Ti, 0.30 mass% or less Zr, 0.10 mass% or less In, and 0.10 mass% or less Sn, with the remainder being aluminum and unavoidable impurities; The brazing material contains 4.00 to 13.00 mass % of Si, more than 0.03 mass % to 3.00 mass % of Mg, more than 0.03 mass % to 3.00 mass % of Cr, Mass% or less and one or more of more than 0.03 mass% Li and not more than 3.00 mass% Ca, with the remainder being aluminum and unavoidable impurities. Brazing heat reduces the amount of heat generated before brazing. Brazing material surface An oxide containing one or more of Mg, Li and Ca, the volume change rate of which is 0.990 or less relative to the surface oxide film. Brazing material side An aluminum alloy brazing sheet is formed on the surface, The aluminum alloy brazing sheet before brazing heat The brazing material The atomic molar ratio of Mg, Li, and Ca to Al in the oxide formed on the surface is 0.5 or less. The present invention provides an aluminum alloy brazing sheet characterized by the above.

[0010] The present invention (2) also provides an aluminum alloy brazing sheet according to (1), characterized in that the aluminum alloy brazing sheet is a two-layer material in which the brazing material is clad on one side of the core material.

[0011] The present invention (3) also provides an aluminum alloy brazing sheet according to (1), characterized in that the aluminum alloy brazing sheet is a three-layer material in which the brazing material is clad on both sides of the core material.

[0012] The present invention (4) also provides a three-layer material in which the aluminum alloy brazing sheet is a three-layer material in which one surface of the core material is clad with the brazing material and the other surface of the core material is clad with a skin material, The skin material is an aluminum alloy skin material made of aluminum or an aluminum alloy containing 6.00 mass% or less of Zn, with the remainder being aluminum and unavoidable impurities; The present invention provides an aluminum alloy brazing sheet characterized by the above (1).

[0013] The present invention (5) also provides an aluminum alloy brazing sheet according to any one of (1) to (4), wherein the core material further contains one or more of 3.00 mass% or less Mg, 3.00 mass% or less Li, and 3.00 mass% or less Ca.

[0014] The present invention (6) provides an aluminum alloy brazing sheet according to any one of (1) to (5), characterized in that the core material further contains 1.00 mass % or less of Bi.

[0015] The present invention (7) provides the aluminum alloy brazing sheet according to any one of (1) to (6), characterized in that the brazing filler metal further contains 1.00 mass % or less of Bi.

[0016] The present invention (8) provides an aluminum alloy brazing sheet according to any one of (1) to (7), characterized in that the brazing material further contains one or more of 0.05 mass% or less Na, 0.05 mass% or less Sr, 0.05 mass% or less Sb, 8.00 mass% or less Zn, 4.00 mass% or less Cu, 1.00 mass% or less Fe, 1.00 mass% or less Mn, 0.30 mass% or less Cr, 0.30 mass% or less Ti, 0.30 mass% or less Zr, 0.10 mass% or less In, and 0.10 mass% or less Sn.

[0017] The present invention (9) provides an aluminum alloy brazing sheet according to any one of (4) to (8), characterized in that the skin further contains one or more of 2.00 mass% or less Mn, 3.00 mass% or less Mg, 5.00 mass% or less Si, 1.50 mass% or less Fe, 1.00 mass% or less Cu, 0.30 mass% or less Ti, 0.30 mass% or less Zr, 0.30 mass% or less Cr, 0.10 mass% or less In, and 0.10 mass% or less Sn.

[0018] The present invention (10) also provides an aluminum alloy brazing sheet according to any one of (1) to (9), characterized in that the thickness of an oxide formed on the surface of the brazing material of the aluminum alloy brazing sheet is 50 nm or less.

[0019] The present invention (11) also relates to a method for producing an aluminum alloy brazing sheet, which comprises at least hot working and cold working on (1) a laminate in which brazing material ingots / core material ingots are laminated in this order, (2) a laminate in which brazing material ingots / core material ingots / brazing material ingots are laminated in this order, or (3) a laminate in which brazing material ingots / core material ingots / skin material ingots are laminated in this order, to obtain an aluminum alloy brazing sheet, the core ingot is an aluminum alloy containing aluminum or one or more of 1.50 mass% or less Fe, 1.50 mass% or less Si, 2.00 mass% or less Cu, 2.00 mass% or less Mn, 3.00 mass% or less Zn, 0.30 mass% or less Cr, 0.30 mass% or less Ti, 0.30 mass% or less Zr, 0.10 mass% or less In, and 0.10 mass% or less Sn, with the remainder being aluminum and unavoidable impurities; The brazing filler metal ingot is an aluminum alloy containing 4.00 to 13.00 mass% Si, one or more of more than 0.03 mass% and not more than 3.00 mass% Mg, more than 0.03 mass% and not more than 3.00 mass% Li, and more than 0.03 mass% and not more than 3.00 mass% Ca, with the remainder being aluminum and unavoidable impurities; The ingot for skin material is aluminum or an aluminum alloy containing 6.00 mass% or less of Zn, with the remainder being aluminum and unavoidable impurities. in can be, Between passes of rolling in cold working, intermediate annealing is performed by heating at 250 to 450°C for 1 hour or more in an atmosphere controlled at an oxygen concentration of 10,000 ppm or less and a dew point of 20°C or less, or after the last cold working pass, final annealing is performed by heating at 250 to 450°C for 1 hour or more in an atmosphere controlled at an oxygen concentration of 10,000 ppm or less and a dew point of 20°C or less, or both between passes of rolling in cold working and after the last cold working pass, annealing is performed by heating at 250 to 450°C for 1 hour or more in an atmosphere controlled at an oxygen concentration of 10,000 ppm or less and a dew point of 20°C or less; Due to An aluminum alloy brazing sheet in which, by brazing heat, an oxide containing any one or more of Mg, Li and Ca is formed on the surface of the brazing material side, the volume change rate of which is 0.990 or less relative to the surface oxide film on the surface of the brazing material side before brazing heat, The atomic molar ratio of Mg, Li and Ca to Al in the oxide formed on the surface of the brazing material of the aluminum alloy brazing sheet before brazing heating is 0.5 or less. Obtaining aluminum alloy brazing sheet The present invention provides a method for producing an aluminum alloy brazing sheet, characterized by the above.

[0020] The present invention (12) also provides a method for producing an aluminum alloy brazing sheet according to (11), wherein the core ingot further contains one or more of 3.00 mass% or less Mg, 3.00 mass% or less Li, and 3.00 mass% or less Ca.

[0021] The present invention (13) also provides a method for producing an aluminum alloy brazing sheet according to (11) or (12), characterized in that either the core material ingot or the brazing material ingot further contains 1.00 mass% or less of Bi.

[0022] The present invention (14) also provides a method for producing an aluminum alloy brazing sheet according to any one of (11) to (13), characterized in that the brazing material ingot further contains one or more of 0.05 mass% or less Na, 0.05 mass% or less Sr, 0.05 mass% or less Sb, 8.00 mass% or less Zn, 4.00 mass% or less Cu, 1.00 mass% or less Fe, 1.00 mass% or less Mn, 0.30 mass% or less Cr, 0.30 mass% or less Ti, 0.30 mass% or less Zr, 0.10 mass% or less In, and 0.10 mass% or less Sn.

[0023] The present invention (15) also provides a method for producing an aluminum alloy brazing sheet according to any one of (11) to (14), characterized in that the ingot for skin material further contains one or more of 2.00 mass% or less Mn, 3.00 mass% or less Mg, 5.00 mass% or less Si, 1.50 mass% or less Fe, 1.00 mass% or less Cu, 0.30 mass% or less Ti, 0.30 mass% or less Zr, 0.30 mass% or less Cr, 0.10 mass% or less In, and 0.10 mass% or less Sn.

[0024] The present invention (16) also provides a method for producing an aluminum alloy brazing sheet according to any one of (11) to (15), characterized in that the brazing material surface of the clad material is etched using either an acidic aqueous solution or an alkaline aqueous solution, or both an acidic aqueous solution and an alkaline aqueous solution, after intermediate annealing if intermediate annealing is performed, after final annealing if final annealing is performed, or after either or both of intermediate annealing and final annealing if both intermediate annealing and final annealing are performed. Effect of the Invention

[0025] According to the present invention, it is possible to provide an aluminum alloy brazing sheet having excellent brazing properties in brazing in an inert gas atmosphere without using flux, and a method for manufacturing the same. [Brief description of the drawings]

[0026] [Figure 1] FIG. 2 is a diagram showing the assembly of gap filling test pieces in the examples and comparative examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0027] Mg, Li and Ca destroy the film-like oxide formed on the surface of the brazing material during brazing heating, effectively exposing the new surface of the molten brazing material. Since Mg, Li and Ca have smaller oxide formation energy than Al, they reduce the film-like oxide mainly composed of Al during brazing heating, forming particulate oxides containing Mg, Li and Ca. In particular, when the brazing sheet brazing material contains more than 0.03 mass% of any one or more of Mg, Li and Ca, Mg, Li and Ca are sufficiently diffused on the surface of the mating material (e.g., 3003 material) to which the brazing sheet is joined, and oxide particles containing any one or more of Mg, Li and Ca are formed in the mating material 3003 material. This causes a volume change in the oxide on the surface of the mating material, and good brazing properties can be obtained even in joints with large gaps.

[0028] The aluminum alloy brazing sheet of the present invention is an aluminum alloy brazing sheet used for brazing in an inert gas atmosphere without using a flux, At least one side of the core material is clad with a brazing material; the core material is an aluminum alloy core material containing aluminum or one or more of 1.50 mass% or less Fe, 1.50 mass% or less Si, 2.00 mass% or less Cu, 2.00 mass% or less Mn, 3.00 mass% or less Zn, 0.30 mass% or less Cr, 0.30 mass% or less Ti, 0.30 mass% or less Zr, 0.10 mass% or less In, and 0.10 mass% or less Sn, with the remainder being aluminum and unavoidable impurities; The brazing filler metal is an aluminum alloy brazing filler metal containing 4.00 to 13.00 mass% Si, one or more of more than 0.03 mass% to 3.00 mass% Mg, more than 0.03 mass% to 3.00 mass% Li, and more than 0.03 mass% to 3.00 mass% Ca, with the remainder being aluminum and unavoidable impurities; An aluminum alloy brazing sheet in which, by brazing heat, an oxide containing any one or more of Mg, Li and Ca is formed on the surface, the volume change rate of which is 0.990 or less relative to the surface oxide film before brazing heat, the atomic molar ratio of Mg, Li, and Ca to Al in the oxide formed on the surface of the aluminum alloy brazing sheet before brazing heating is 0.5 or less; The aluminum alloy brazing sheet is characterized by the above.

[0029] The aluminum alloy brazing sheet of the present invention is an aluminum alloy brazing sheet used for brazing in an inert gas atmosphere without using flux. The aluminum alloy brazing sheet of the present invention is a clad material in which a brazing material having the chemical composition shown below is clad on at least one side of a core material having the chemical composition shown below. The aluminum alloy brazing sheet of the present invention is (1) a two-layer material in which a brazing material is clad on one side of a core material, (2) a three-layer material in which a brazing material is clad on both sides of a core material, or (3) a three-layer material in which a brazing material is clad on one side of a core material and a skin material is clad on the other side of the core material.

[0030] The core material for the aluminum alloy brazing sheet of the present invention is an aluminum alloy core material containing aluminum, or one or more of 1.50 mass% or less Fe, 1.50 mass% or less Si, 2.00 mass% or less Cu, 2.00 mass% or less Mn, 3.00 mass% or less Zn, 0.30 mass% or less Cr, 0.30 mass% or less Ti, 0.30 mass% or less Zr, 0.10 mass% or less In and 0.10 mass% or less Sn, with the remainder being aluminum and unavoidable impurities.

[0031] When the core material is made of aluminum, the purity of the aluminum is not particularly limited, but is preferably 99.0% by mass or more, and particularly preferably 99.5% by mass or more.

[0032] In the aluminum alloy forming the core material, Fe contributes to improving the strength. When the core material contains Fe, the Fe content in the core material is 1.50 mass% or less, preferably 0.10 to 0.70 mass%, and particularly preferably 0.20 to 0.60 mass%. When the Fe content in the core material is within the above range, the strength of the core material is high. On the other hand, when the Fe content in the core material exceeds the above range, the corrosion resistance is reduced and large precipitates are easily generated.

[0033] In the aluminum alloy forming the core material, Si contributes to improving the strength. When the core material contains Si, the Si content in the core material is 1.50 mass% or less, preferably 0.10 to 1.00 mass%, and particularly preferably 0.30 to 0.75 mass%. When the Si content in the core material is within the above range, the strength of the core material is high. On the other hand, when the Si content in the core material exceeds the above range, the melting point becomes too low, causing local melting during brazing, causing deformation of the core material and reducing corrosion resistance.

[0034] In the aluminum alloy forming the core material, Cu contributes to improving strength and adjusting potential. When the core material contains Cu, the Cu content in the core material is 2.00 mass% or less, preferably 0.10 to 1.00 mass%, and particularly preferably 0.15 to 0.80 mass%. When the Cu content in the core material is within the above range, the strength of the core material is high. On the other hand, when the Cu content in the core material exceeds the above range, intergranular corrosion is likely to occur and the melting point becomes too low.

[0035] In the aluminum alloy forming the core material, Mn contributes to improving strength and adjusting potential. When the core material contains Mn, the Mn content in the core material is 2.00 mass% or less, preferably 0.30 to 1.80 mass%, and particularly preferably 0.30 to 1.50 mass%. When the Mn content in the core material is within the above range, the strength of the core material is increased and a potential adjustment effect is obtained. When the Mn content in the core material exceeds the above range, cracks are likely to occur during material rolling.

[0036] In the aluminum alloy forming the core material, Zn contributes to potential adjustment. When the core material contains Zn, the Zn content in the core material is 3.00 mass% or less, preferably 0.50 to 3.00 mass%, and particularly preferably 1.50 to 3.00 mass%. When the Zn content in the core material is within the above range, a potential adjustment effect is obtained. On the other hand, when the Zn content in the core material exceeds the above range, the natural electrode potential becomes too low, and the corrosion resistance decreases.

[0037] In the aluminum alloy forming the core material, Cr improves strength by solid solution strengthening, and also precipitates fine Al-Cr compounds, which act to coarsen crystal grains after brazing. The Cr content in the core material is 0.30 mass% or less, preferably 0.10 to 0.20 mass%. When the Cr content in the core material is within the above range, the strength of the core material is high. On the other hand, when the Cr content in the core material exceeds the above range, large intermetallic compounds are easily formed during casting, and the plastic workability is reduced.

[0038] In the aluminum alloy forming the core material, Ti improves strength by solid solution strengthening, and is distributed in layers to form high and low potential layers in the core material, thereby changing the corrosion form from pitting to layered corrosion, thereby improving corrosion resistance. The Ti content in the core material is 0.30 mass% or less, preferably 0.10 to 0.20 mass%, and particularly preferably 0.12 to 0.18 mass%. When the Ti content in the core material is within the above range, the strength of the core material is increased and the corrosion resistance is improved. On the other hand, when the Ti content in the core material exceeds the above range, giant intermetallic compounds are easily formed during casting, and the plastic workability is reduced.

[0039] In the aluminum alloy forming the core material, Zr improves strength by solid solution strengthening, and also precipitates fine Al-Zr compounds, which act to coarsen crystal grains after brazing. The Zr content in the core material is 0.30 mass% or less, preferably 0.10 to 0.20 mass%. When the Zr content in the core material is within the above range, the strength of the core material is increased, and the effect of coarsening crystal grains after brazing is obtained. On the other hand, when the Zr content in the core material exceeds the above range, giant intermetallic compounds are easily formed during casting, and plastic workability is reduced.

[0040] In the aluminum alloy forming the core material, In contributes to potential adjustment. When the core material contains In, the In content in the core material is 0.10 mass% or less, preferably 0.01 to 0.03 mass%. When the In content in the core material is within the above range, a potential adjustment effect is obtained. On the other hand, when the In content in the core material exceeds the above range, the natural electrode potential becomes too low, and the corrosion resistance decreases.

[0041] In the aluminum alloy forming the core material, Sn contributes to potential adjustment. When the core material contains Sn, the Sn content in the core material is 0.10 mass% or less, preferably 0.01 to 0.10 mass%. When the Sn content in the core material is within the above range, a potential adjustment effect is obtained. On the other hand, when the Sn content in the core material exceeds the above range, the natural electrode potential becomes too low, resulting in low corrosion resistance.

[0042] The core material may contain Bi. In the aluminum alloy forming the core material, when the brazing material melts during brazing heating and melts a part of the core material, Bi acts to suppress the decrease in the Bi concentration of the brazing material, and exerts the effect of lowering the surface tension of the Al-Si molten brazing material. When the core material contains Bi, the Bi content in the core material is 1.00 mass% or less, preferably 0.10 to 1.00 mass%. When the Bi content in the core material is within the above range, the effect of melting in the brazing material and lowering the surface tension is obtained. On the other hand, when the Bi content in the core material exceeds the above range, rolling of the material becomes difficult.

[0043] The core material may contain one or more of Mg, Li, and Ca. When the core material contains Mg, the Mg content in the core material is 3.00 mass% or less, preferably 0.10 to 1.80 mass%. When the core material contains Li, the Li content in the core material is 3.00 mass% or less, preferably 0.10 to 1.80 mass%. When the core material contains Ca, the Ca content in the core material is 3.00 mass% or less, preferably 0.10 to 1.80 mass%. When the core material contains Ca, the Ca content in the core material is 3.00 mass% or less, preferably 0.10 to 1.80 mass%. When the core material contains Mg, Li, or Ca in the above range, when the brazing material melts during brazing heating and a part of the core material melts, the concentration of Mg, Li, or Ca in the brazing material is suppressed from decreasing, and the volume change rate of the oxide formed by oxidation of Mg, Li, or Ca on the brazing material surface is 0.990 or less, and the effect of destroying the oxide film of the brazing sheet and the mating material by Mg, Li, or Ca is enhanced, and excellent brazing properties are obtained. On the other hand, if the content of Mg, Li, or Ca in the core material exceeds the above range, the melting point of the core material will be too low, causing local melting in the core material during brazing heating, deforming the core material, and causing erosion of the core material by the molten brazing material, resulting in reduced brazing joinability and corrosion resistance.

[0044] The core material may contain up to 0.05 mass% of Ag, B, Be, Cd, Co, Ga, Ge, Mo, Na, Ni, P, Pb, Sr, V, Hg, and Y as unavoidable impurities.

[0045] The brazing material for the aluminum alloy brazing sheet of the present invention is (i) 4.0 to 13.0 mass% Si; (ii) one or more of more than 0.03% by mass and not more than 3.00% by mass of Mg, more than 0.03% by mass and not more than 3.00% by mass of Li, and more than 0.03% by mass and not more than 3.00% by mass of Ca; The aluminum alloy brazing filler metal contains the above-mentioned elements, with the remainder being aluminum and unavoidable impurities.

[0046] The brazing filler metal contains Si as an essential element. The Si content in the brazing filler metal is 4.00 to 13.00 mass%, and particularly preferably 4.50 to 12.00 mass%. When the Si content in the brazing filler metal is within the above range, a sufficient liquid phase necessary for brazing bonding can be obtained. On the other hand, if the Si content in the core material is less than the above range, the amount of liquid phase is insufficient, and if it exceeds the above range, cracks are likely to occur during material production, making it difficult to produce the brazing sheet.

[0047] The brazing filler metal contains one or more of Mg, Li, and Ca.

[0048] When the brazing material contains Mg, the Mg content in the brazing material is more than 0.03 mass% and not more than 3.00 mass%, preferably 0.10 to 1.80 mass%, and particularly preferably 0.60 to 1.20 mass%. When the brazing material contains Li, the Li content in the brazing material is more than 0.03 mass% and not more than 3.00 mass%, preferably 0.04 to 1.80 mass%, and particularly preferably 0.10 to 1.80 mass%. When the brazing material contains Ca, the Ca content in the brazing material is more than 0.03 mass% and not more than 3.00 mass%, preferably 0.05 to 1.80 mass%, and particularly preferably 0.10 to 1.80 mass%. By having the content of Mg, Li, or Ca in the brazing material within the above range, the volume change rate of the oxide formed by oxidation of Mg, Li, or Ca during brazing heat is 0.990 or less, the effect of Mg, Li, or Ca in destroying the oxide film of the brazing sheet and the mating material is enhanced, and excellent brazing properties are obtained. On the other hand, if the content of Mg, Li, and Ca in the core material is less than the above range, the effect of Mg, Li, and Ca in destroying the oxide film of the brazing sheet and the mating material is poor, and if it exceeds the above range, the oxidation of Mg, Li, and Ca progresses during brazing heat, and oxides with a volume change rate exceeding 0.990 are formed.

[0049] The brazing material may contain Bi. In the aluminum alloy forming the brazing material, Bi exerts an effect of lowering the surface tension of the Al-Si molten brazing material. When the brazing material contains Bi, the Bi content in the brazing material is 1.00 mass% or less, preferably 0.50 mass% or less, more preferably 0.05 to 0.40 mass%, and particularly preferably 0.10 to 0.30 mass%. When the Bi content in the brazing material is within the above range, the effect of lowering the surface tension is easily obtained. On the other hand, when the Bi content in the brazing material exceeds the above range, the brazing material surface after brazing turns black, and the brazing property is reduced.

[0050] The brazing material may contain one or more of Na, Sr, and Sb. In the aluminum alloy forming the brazing material, Na, Sr, and Sb have the effect of refining Si particles in the brazing material and enhancing the fluidity of the brazing material. When the brazing material contains Na, the Na content in the brazing material is 0.05 mass% or less, preferably 0.005 to 0.04 mass%, and particularly preferably 0.007 to 0.04 mass%. When the brazing material contains Sr, the Sr content in the brazing material is 0.05 mass% or less, preferably 0.005 to 0.04 mass%, and particularly preferably 0.005 to 0.02 mass%. When the brazing material contains Sb, the Sb content in the brazing material is 0.05 mass% or less, preferably 0.005 to 0.04 mass%.

[0051] The brazing material may contain one or two of Zn and Cu. In the aluminum alloy forming the brazing material, Zn and Cu lower the melting point of the brazing material, enabling brazing at a temperature lower than 600°C, which is a general brazing temperature. When the brazing material contains Zn, the Zn content in the brazing material is preferably 8.00 mass% or less, more preferably 1.00 to 8.00 mass%, particularly preferably 2.00 to 8.00 mass%, and even more preferably 3.00 to 5.00 mass%, in order to easily obtain the effect of lowering the melting point of the brazing material. On the other hand, when the Zn content in the brazing material exceeds 8.00 mass%, cracks occur in the brazing material during cold rolling, and a sound plate material cannot be obtained. In addition, when the brazing material contains Zn, the Zn content in the brazing material is preferably 3.00 mass% or less, in order to easily obtain the effect of preventing corrosion of the core material by making the potential of the brazing material base and corroding preferentially with respect to the core material. When the brazing filler metal contains Cu, the Cu content in the brazing filler metal is 4.00 mass% or less, preferably 0.50 to 4.00 mass%, and particularly preferably 1.00 to 2.50 mass%. When the Cu content in the brazing filler metal is within the above range, the effect of lowering the melting point of the brazing filler metal is enhanced. On the other hand, when the Cu content in the brazing filler metal exceeds the above range, cracks occur in the brazing filler metal during cold rolling, and a sound plate material cannot be obtained.

[0052] The brazing material may contain Fe. In the aluminum alloy forming the brazing material, Fe crystallizes a relatively coarse Al-Fe compound, which acts to refine the crystal grains of the brazing material after brazing. When the brazing material contains Fe, the Fe content in the brazing material is 1.00 mass% or less, preferably 0.10 to 0.50 mass%, and particularly preferably 0.20 to 0.50 mass%. When the Fe content in the brazing material is within the above range, the effect of refining the crystal grains can be easily obtained. On the other hand, when the Fe content in the brazing material exceeds the above range, a large intermetallic compound is easily formed during casting, and the plastic workability is reduced.

[0053] The brazing material may contain one or more of Mn, Cr, Ti, and Zr. In the aluminum alloy forming the brazing material, Mn, Cr, Ti, and Zr precipitate fine compounds of Al-Mn, Al-Cr, Al-Ti, and Al-Zr, respectively, and act to coarsen grains after brazing. When the brazing material contains Mn, the content of Mn in the brazing material is 1.00 mass% or less, preferably 0.10 to 0.60 mass%. By having the Mn content in the brazing material within the above range, the effect of coarsening grains can be easily obtained. On the other hand, when the Mn content in the brazing material exceeds the above range, macro intermetallic compounds are easily formed during casting, and the plastic workability is reduced. When the brazing material contains Cr, the content of Cr in the brazing material is 0.30 mass% or less, preferably 0.01 to 0.03 mass%. By having the Cr content in the brazing material within the above range, the effect of coarsening grains can be easily obtained. On the other hand, if the Cr content in the brazing material exceeds the above range, a giant intermetallic compound is easily formed during casting, and the plastic workability is reduced. When the brazing material contains Ti, the Ti content in the brazing material is 0.30 mass% or less, preferably 0.10 mass% or less, and particularly preferably 0.01 to 0.03 mass%. By having the Ti content in the brazing material within the above range, the effect of grain coarsening is easily obtained. On the other hand, if the Ti content in the brazing material exceeds the above range, a giant intermetallic compound is easily formed during casting, and the plastic workability is reduced. When the brazing material contains Zr, the Zr content in the brazing material is 0.30 mass% or less, preferably 0.01 to 0.03 mass%. By having the Zr content in the brazing material within the above range, the effect of grain coarsening is easily obtained. On the other hand, if the Zr content in the brazing material exceeds the above range, a giant intermetallic compound is easily formed during casting, and the plastic workability is reduced. The above-mentioned action is utilized to adjust the crystal grain size after brazing, and within the above-mentioned range, the effect of the present invention can be sufficiently obtained.

[0054] The brazing material may contain In. In the aluminum alloy forming the brazing material, In makes the potential of the brazing material lower and corrodes preferentially with respect to the core material, thereby exerting the effect of preventing corrosion of the core material. When the brazing material contains In, the In content in the brazing material is 0.10 mass% or less, preferably 0.01 to 0.03 mass%, and particularly preferably 0.02 to 0.03 mass%. By having the In content in the brazing material within the above range, the effect of adjusting the potential can be easily obtained. On the other hand, if the In content in the brazing material exceeds the above range, the natural electrode potential becomes too low, and the corrosion resistance decreases.

[0055] The brazing material may contain Sn. In the aluminum alloy forming the brazing material, Sn makes the potential of the brazing material lower and corrodes preferentially with respect to the core material, thereby exerting the effect of protecting the core material from corrosion. When the brazing material contains Sn, the Sn content in the brazing material is 0.10 mass% or less, preferably 0.01 to 0.05 mass%. By having the Sn content in the brazing material within the above range, the effect of adjusting the potential can be easily obtained. On the other hand, if the Sn content in the brazing material exceeds the above range, the natural electrode potential becomes too low, and the corrosion resistance decreases.

[0056] The brazing filler metal may contain 0.05 mass % or less of Ag, B, Be, Cd, Co, Ga, Ge, Mo, Ni, P, Pb, V, Hg, and Y as unavoidable impurities.

[0057] The skin material of the aluminum alloy brazing sheet of the present invention contains aluminum or 6.00 mass% or less of Zn, with the remainder being aluminum and unavoidable impurities. R The aluminum alloy brazing sheet of the present invention is an aluminum alloy skin material. ToIn the brazing process, the surface material is clad, and the sacrificial anticorrosive effect of the surface material can further improve the corrosion resistance of the aluminum product after brazing. The aluminum alloy brazing sheet of the present invention forms an oxide containing one or more of Mg, Li and Ca, which has a volume change rate after brazing heat to the surface oxide film before brazing heat of 0.990 or less, preferably 0.700 to 0.970, more preferably 0.700 to 0.950, and particularly preferably 0.800 to 0.900, on the surface of the brazing material side during brazing heat, and thus has excellent brazing properties because the newly formed surface of the brazing material is exposed during brazing heat in an inert gas atmosphere without using flux. Therefore, the aluminum alloy brazing sheet of the present invention has the above-mentioned effects of the present invention whether the surface of the core material opposite to the brazing material is clad with a skin material or not.

[0058] When the skin material is made of aluminum, the purity of the aluminum is not particularly limited, but is preferably 99.0% by mass or more, and particularly preferably 99.5% by mass or more.

[0059] When the skin material is made of an aluminum alloy containing Zn, the Zn content in the skin material is 6.00 mass% or less, preferably 3.00 mass% or less. By having the Zn content in the skin material within the above range, the sacrificial corrosion protection effect is enhanced. On the other hand, if the Zn content in the skin material exceeds the above range, the potential of the skin material is excessively reduced, and there is a risk of the corrosion progressing faster.

[0060] The skin material may contain Mn. In the aluminum alloy forming the skin material, Mn contributes to improving the strength. When the skin material contains Mn, the Mn content in the skin material is 2.00 mass% or less, preferably 0.30 to 1.80 mass%. By having the Mn content in the skin material within the above range, the effect of improving the strength can be easily obtained. On the other hand, if the Mn content in the skin material exceeds the above range, cracks are likely to occur during rolling of the material.

[0061] The skin material may contain Mg. In the aluminum alloy forming the skin material, Mg contributes to improving the strength. When the skin material contains Mg, the Mg content in the skin material is 3.00 mass% or less, preferably 0.30 to 1.80 mass%, and particularly preferably 0.40 to 1.80 mass%. By having the Mg content in the skin material within the above range, the effect of improving the strength can be easily obtained. On the other hand, if the Mg content in the skin material exceeds the above range, cracks are likely to occur during rolling of the material.

[0062] The cladding material may contain Si. In the aluminum alloy forming the cladding material, Si contributes to improving the strength. When the cladding material contains Si, the Si content in the cladding material is 5.00 mass% or less, preferably 0.10 to 1.50 mass%, more preferably 0.10 to 1.00 mass%, and particularly preferably 0.20 to 1.00 mass%. When the Si content in the cladding material is within the above range, the strength of the cladding material is increased. In addition, the Si content in the cladding material is 1.50 to 5.00 mass%, particularly preferably 2.50 to 4.50 mass%, and when the Si content is in the range of 1.50 to 5.00%, the cladding material becomes semi-molten during brazing heating, and a small amount of liquid phase brazing material is supplied to improve brazing property when the cladding surface becomes the brazing surface. When the Si content in the cladding material exceeds the above range, the melting point becomes too low, melting occurs during brazing, and deformation of the cladding material occurs.

[0063] The cladding material may contain Fe. In the aluminum alloy forming the cladding material, Fe contributes to improving the strength. When the cladding material contains Fe, the Fe content in the cladding material is 1.50 mass% or less, preferably 0.10 to 0.70 mass%, and particularly preferably 0.10 to 0.50 mass%. When the Fe content in the cladding material is within the above range, the effect of improving the strength can be easily obtained. On the other hand, when the Fe content in the cladding material exceeds the above range, the corrosion resistance decreases and giant precipitates are easily generated.

[0064] The cladding material may contain Cu. In the aluminum alloy forming the cladding material, Cu contributes to improving the strength. When the cladding material contains Cu, the Cu content in the cladding material is 1.00 mass% or less, preferably 0.10 to 1.00 mass%. By having the Cu content in the cladding material within the above range, the effect of improving the strength can be easily obtained. On the other hand, if the Cu content in the cladding material exceeds the above range, intergranular corrosion is likely to occur.

[0065] The skin material may contain one or more of Ti, Zr, and Cr. In the aluminum alloy forming the skin material, Ti, Zr, and Cr exert the effect of improving strength by solid solution strengthening. When the skin material contains Ti, the Ti content in the skin material is 0.30 mass% or less, preferably 0.10 to 0.20 mass%. When the skin material contains Zr, the Zr content in the skin material is 0.30 mass% or less, preferably 0.10 to 0.20 mass%. When the skin material contains Cr, the Cr content in the skin material is 0.30 mass% or less, preferably 0.10 to 0.20 mass%. When the Ti, Zr, or Cr in the skin material is in the above range, the effect of improving strength can be easily obtained. On the other hand, when the Ti, Zr, or Cr in the skin material exceeds the above range, a giant intermetallic compound is easily formed during casting, and the plastic workability is reduced.

[0066] The skin material may contain In. In the aluminum alloy forming the skin material, In has the effect of making the potential of the skin material lower and corroding preferentially with respect to the core material, thereby preventing corrosion of the core material. When the skin material contains In, the In content in the skin material is 0.10 mass% or less, preferably 0.01 to 0.03 mass%. By having the In content in the skin material within the above range, the effect of adjusting the potential can be easily obtained. On the other hand, if the In content in the skin material exceeds the above range, the natural electrode potential becomes too low, and the corrosion resistance decreases.

[0067] The skin material may contain Sn. In the aluminum alloy forming the skin material, Sn makes the potential of the skin material lower and corrodes preferentially with respect to the core material, thereby preventing the core material from corroding. When the skin material contains Sn, the Sn content in the skin material is 0.10 mass% or less, preferably 0.01 to 0.05 mass%. By having the Sn content in the skin material within the above range, the effect of adjusting the potential can be easily obtained. On the other hand, if the Sn content in the skin material exceeds the above range, the natural electrode potential becomes too low, and the corrosion resistance decreases.

[0068] The cladding material may contain 0.05 mass% or less of the following elements as unavoidable impurities: Ag, B, Be, Bi, Ca, Cd, Co, Ga, Ge, Li, Mo, Na, Ni, P, Pb, Sr, V, and Hg.

[0069] The aluminum alloy brazing sheet of the present invention is an aluminum alloy brazing sheet on which oxide particles containing any one or more of Mg, Li and Ca are formed on the surface, the volume change rate of which is 0.990 or less, preferably 0.700 to 0.970, more preferably 0.700 to 0.950, and particularly preferably 0.800 to 0.900, relative to the surface oxide film before brazing heat by brazing heat in an inert gas atmosphere without using flux. In brazing heat in an inert gas atmosphere without using flux, the volume change rate of the oxide containing Mg, Li and Ca after brazing heat relative to the surface oxide before brazing heat is within the above range, and particulate oxide containing Mg, Li and Ca is formed, so that the newly formed surface of the brazing material is effectively exposed during brazing heat, and thus the aluminum alloy brazing sheet has excellent brazeability.

[0070] On the other hand, in the brazing heating in an inert gas atmosphere without using flux, if the volume change rate of the oxide containing one or more of Mg, Li and Ca after brazing heating relative to the surface oxide film before brazing heating is larger than the above range, the newly formed surface of the brazing material is difficult to expose during brazing heating. In the present invention, the volume change rate of the oxide containing one or more of Mg, Li and Ca formed by brazing heating is the volume change rate relative to the oxide film formed on the brazing material surface before brazing, and is a value calculated by the formula "volume per oxygen atom of oxide particles containing one or more of Mg, Li and Ca formed by brazing heating / volume per oxygen atom of oxide film formed on the brazing material surface before brazing". In the formula, the volume per oxygen atom is calculated by dividing the molecular weight of the oxide by the density of the oxide.

[0071] Mg, Li, and Ca have a smaller free energy of oxide formation than Al, and can reduce oxide films. They can also form oxides with a volume change rate of 0.990 or less, making them effective elements for exposing the new surface of the brazing material during brazing heating in an inert gas atmosphere without using flux. For example, the volume change rate of MgO is 0.994, but MgAl 2 O 4 The volume change rate of Ba is 0.863, which is smaller than 0.990. On the other hand, although Ba, Th, Nd, etc. are elements with a smaller oxide formation free energy than Al, they are not effective elements to be contained because there are no oxides with a volume change rate of 0.990 or less. For example, BaO, BaAl 2 O 4 The volume change rates of Ba are 2.366 and 1.377, respectively, and there is no oxide of Ba with a volume change rate of 0.990 or less.

[0072] An oxide film is formed on the surface of the brazing material of the aluminum alloy brazing sheet of the present invention. The molar ratio of Mg, Li, and Ca to Al in terms of atoms of the oxide film formed on the surface of the brazing material of the aluminum alloy brazing sheet of the present invention is 0.50 or less. When the molar ratio of Mg, Li, and Ca to Al in terms of atoms (e.g., Mg / Al) of the oxide film formed on the surface of the brazing material is within the above range, the volume change rate of the oxide containing Mg, Li, and Ca formed by brazing heating on the oxide film formed on the surface of the brazing material before brazing is 0.990 or less. In addition, when the oxide film formed on the surface of the brazing material of the aluminum alloy brazing sheet of the present invention contains two or more elements of Mg, Li, and Ca, the molar ratio of Mg, Li, and Ca to Al in terms of atoms of 0.50 or less means that the molar ratio of Mg, Li, and Ca to Al in terms of atoms of 0.5 or less for each of Mg, Li, and Ca.

[0073] The thickness of the oxide film formed on the surface of the brazing material of the aluminum alloy brazing sheet of the present invention is preferably 50 nm or less, more preferably 10 nm or less, because the oxide film is easily destroyed. If the thickness of the oxide film formed on the surface of the brazing material exceeds 50 nm, the destruction of the oxide film becomes difficult to proceed.

[0074] The aluminum alloy brazing sheet of the present invention is suitably produced by the method for producing an aluminum alloy brazing sheet of the present invention described below.

[0075] The method for producing an aluminum alloy brazing sheet of the present invention comprises at least hot working and cold working on (1) a laminate in which brazing filler ingot / core ingot are stacked in this order, (2) a laminate in which brazing filler ingot / core ingot / brazing filler ingot are stacked in this order, or (3) a laminate in which brazing filler ingot / core ingot / skin ingot are stacked in this order, to obtain an aluminum alloy brazing sheet, the core ingot is an aluminum alloy containing aluminum or one or more of 1.50 mass% or less Fe, 1.50 mass% or less Si, 2.00 mass% or less Cu, 2.00 mass% or less Mn, 3.00 mass% or less Zn, 0.30 mass% or less Cr, 0.30 mass% or less Ti, 0.30 mass% or less Zr, 0.10 mass% or less In, and 0.10 mass% or less Sn, with the remainder being aluminum and unavoidable impurities; The ingot for brazing filler metal contains 4.00 to 13.00 mass% Si, one or more of more than 0.03 mass% and not more than 3.00 mass% Mg, more than 0.03 mass% and not more than 3.00 mass% Li, and more than 0.03 mass% and not more than 3.00 mass% Ca, with the remainder being aluminum and unavoidable impurities; The ingot for skin material is aluminum or an aluminum alloy containing 6.00 mass% or less of Zn, with the remainder being aluminum and unavoidable impurities. in can be, Between passes of rolling in cold working, intermediate annealing is performed by heating at 250 to 450°C for 1 hour or more in an atmosphere controlled at an oxygen concentration of 10,000 ppm or less and a dew point of 20°C or less, or after the last cold working pass, final annealing is performed by heating at 250 to 450°C for 1 hour or more in an atmosphere controlled at an oxygen concentration of 10,000 ppm or less and a dew point of 20°C or less, or both between passes of rolling in cold working and after the last cold working pass, annealing is performed by heating at 250 to 450°C for 1 hour or more in an atmosphere controlled at an oxygen concentration of 10,000 ppm or less and a dew point of 20°C or less; This is a method for producing an aluminum alloy brazing sheet, characterized by the above.

[0076] The method for producing an aluminum alloy brazing sheet of the present invention is a method for producing an aluminum alloy brazing sheet, which comprises at least hot working and cold working on (1) a laminate in which a brazing material ingot and a core material ingot are superimposed on each other, or (2) a laminate in which a brazing material ingot is superimposed on both sides of a core material ingot, or a laminate in which a brazing material ingot is superimposed on one side of a core material ingot and a skin material ingot is superimposed on the other side of the core material ingot, i.e., (1) a laminate in which brazing material ingot / core material ingot are superimposed in the order of (2) a laminate in which brazing material ingot / core material ingot / brazing material ingot are superimposed in the order of (3) a laminate in which brazing material ingot / core material ingot / skin material ingot are superimposed in the order of

[0077] In the manufacturing method of the aluminum alloy brazing sheet of the present invention, the types and contents of added components in the core ingot, brazing filler metal ingot and skin material ingot are the same as the components and contents of the core ingot, brazing filler metal ingot and skin material in the aluminum alloy brazing sheet of the present invention.

[0078] That is, the core ingot contains aluminum or 1.50 mass% or less, preferably 0.10 to 0.70 mass%, and particularly preferably 0.20 to 0.60 mass% Fe, 1.50 mass% or less, preferably 0.10 to 1.00 mass%, and particularly preferably 0.30 to 0.75 mass% Si, 2.00 mass% or less, preferably 0.10 to 1.00 mass%, and particularly preferably 0.15 to 0.80 mass% Cu, 2.00 mass% or less, preferably 0.30 to 1.80 mass%, and particularly preferably 0.30 to 1.50 mass% Mn, 3.00 mass% or less, preferably 0.50 to 3.00 mass%, and particularly preferably 1.50 to 3.00 mass% Zn, 0.30 mass% or less, preferably 0.10 to 0.20 mass% Cr, 0.30 mass% or less, preferably 0.10 to 0.20 mass% %, particularly preferably 0.12 to 0.18 mass% Ti, 0.30 mass% or less, preferably 0.10 to 0.20 mass% Zr, 0.10 mass% or less, preferably 0.01 to 0.03 mass% In, and 0.10 mass% or less, preferably 0.01 to 0.10 mass% Sn, and optionally 1.00 mass% or less, preferably 0.10 to 1.00 mass% Bi, and optionally 3.00 mass% or less, preferably 0.10 to 1.80 mass% Mg, 3.00 mass% or less, preferably 0.10 to 1.80 mass% Li, and 3.00 mass% or less, preferably 0.10 to 1.80 mass% Ca, with the remainder being aluminum and unavoidable impurities. The core ingot may contain 0.05 mass% or less of Ag, B, Be, Cd, Co, Ga, Ge, Mo, Na, Ni, P, Pb, Sr, V, Hg, and Y as unavoidable impurities.

[0079] The brazing filler metal ingot contains 4.00 to 13.00 mass%, particularly preferably 4.50 to 12.00 mass% Si, more than 0.03 mass% to 3.00 mass%, preferably 0.10 to 1.80 mass%, particularly preferably 0.60 to 1.20 mass% Mg, more than 0.03 mass% to 3.00 mass%, preferably 0.04 to 1.80 mass%, particularly preferably 0.10 to 1.80 mass% Li, and more than 0.03 mass% to 3.00 mass%, preferably 0.05 to 1.80 mass%, particularly preferably 0.10 to 1.80 mass% Ca. and optionally 1.00 mass% or less, preferably 0.50 mass% or less, more preferably 0.05 to 0.40 mass%, and particularly preferably 0.10 to 0.30 mass% of Bi; optionally 0.05 mass% or less, preferably 0.005 to 0.04 mass%, and particularly preferably 0.007 to 0.04 mass% of Na; 0.05 mass% or less, preferably 0.005 to 0.04 mass%, and particularly preferably 0.005 to 0.02 mass% of Sr; 4 mass% Sb, 8.00 mass% or less, preferably 1.00 to 8.00 mass%, more preferably 2.00 to 8.00 mass%, particularly preferably 3.00 to 5.00 mass% Zn, 4.00 mass% or less, preferably 0.50 to 4.00 mass%, particularly preferably 1.00 to 2.50 mass% Cu, 1.00 mass% or less, preferably 0.10 to 0.50 mass%, particularly preferably 0.20 to 0.50 mass% Fe, 1.00 mass% or less, preferably 0.10 to 0.60 mass% Mn, 0.30 mass% or less, preferably 0.0 The aluminum alloy comprises one or more of 1 to 0.03 mass% Cr, 0.30 mass% or less, preferably 0.10 mass% or less, and particularly preferably 0.01 to 0.03 mass% Ti, 0.30 mass% or less, preferably 0.01 to 0.03 mass% Zr, 0.10 mass% or less, preferably 0.01 to 0.03 mass%, and particularly preferably 0.02 to 0.03 mass% In, and 0.10 mass% or less, preferably 0.01 to 0.05 mass% Sn, with the remainder being aluminum and unavoidable impurities.The brazing filler metal ingot may contain one or more of the following elements as unavoidable impurities in an amount of 0.05 mass% or less: Ag, B, Be, Cd, Co, Ga, Ge, Mo, Ni, P, Pb, V, Hg, and Y.

[0080] The ingot for skin material contains aluminum or 6.00 mass% or less, preferably 3.00 mass% or less Zn, and, as necessary, 2.00 mass% or less, 0.30 to 1.80 mass% Mn, 3.00 mass% or less, preferably 0.30 to 1.80 mass%, particularly preferably 0.40 to 1.80 mass% Mg, 5.00 mass% or less, preferably 0.10 to 1.50 mass%, more preferably 0.10 to 1.00 mass%, particularly preferably 0.20 to 1.00 mass% Si, or 5.00 mass% or less, preferably 2.50 to 4.50 mass% Si, 1.50 mass% or less, preferably 0.10 to 0.70 mass%, particularly preferably The aluminum alloy preferably contains one or more of 0.10 to 0.50 mass% Fe, 1.00 mass% or less, preferably 0.10 to 1.00 mass% Cu, 0.30 mass% or less, preferably 0.10 to 0.20 mass% Ti, 0.30 mass% or less, preferably 0.10 to 0.20 mass% Zr, 0.30 mass% or less, preferably 0.10 to 0.20 mass% Cr, 0.10 mass% or less, preferably 0.01 to 0.03 mass% In, and 0.10 mass% or less, preferably 0.01 to 0.05 mass% Sn, with the remainder being aluminum and unavoidable impurities. The ingot for skin material may contain 0.05 mass% or less of Ag, B, Be, Bi, Ca, Cd, Co, Ga, Ge, Li, Mo, Na, Ni, P, Pb, Sr, V, Hg, and Y as unavoidable impurities.

[0081] In the manufacturing method of the aluminum alloy brazing sheet of the present invention, (1) a laminate in which brazing material ingot / core ingot are laminated in this order, (2) a laminate in which brazing material ingot / core ingot / brazing material ingot are laminated in this order, or (3) a laminate in which brazing material ingot / core ingot / skin ingot are laminated in this order, is hot-rolled and cold-rolled. In the hot-rolling, a laminate is made at 400 to 550°C, and then the laminate is worked to a plate thickness of 2 to 3 mm while still hot. In the cold-rolling, rolling is performed in multiple passes in the cold state, and the laminate is worked to a predetermined aluminum alloy brazing sheet thickness.

[0082] In the manufacturing method of the aluminum alloy brazing sheet of the present invention, intermediate annealing is performed between multiple rolling passes in cold working, in which the sheet is heated at 250 to 450 ° C for 1 hour or more in an atmosphere controlled to have an oxygen concentration of 10000 ppm or less and a dew point of 20 ° C or less, or after the last cold working pass, final annealing is performed in which the sheet is heated at 250 to 450 ° C for 1 hour or more in an atmosphere controlled to have an oxygen concentration of 10000 ppm or less and a dew point of 20 ° C or less, or annealing is performed in which the sheet is heated at 250 to 450 ° C for 1 hour or more in an atmosphere controlled to have an oxygen concentration of 10000 ppm or less and a dew point of 20 ° C or less both between rolling passes in cold working and after the last cold working pass. Intermediate annealing or final annealing is a high-temperature process, so it has a large effect on the state of the oxide film. The atmosphere for intermediate annealing or final annealing is an inert gas atmosphere such as nitrogen gas, argon gas, or carbon dioxide gas. By performing intermediate annealing or final annealing in an atmosphere controlled to an oxygen concentration of 10,000 ppm or less and a dew point of 20° C. or less, an aluminum alloy brazing sheet is easily obtained in which oxide particles containing Mg, Li, and Ca are formed on the surface by brazing heating, and the volume change rate relative to the oxide film before brazing heating is 0.990 or less. If the oxygen concentration in the atmosphere during intermediate annealing or final annealing exceeds 10,000 ppm, the growth of the oxide film is promoted and the concentrations of Mg, Li, and Ca in the oxide film are easily increased. If the dew point of the atmosphere during intermediate annealing or final annealing exceeds 20° C., a hydroxide film is easily formed and the oxide film is easily thickened.

[0083] In the manufacturing method of the aluminum alloy brazing sheet of the present invention, the brazing material surface of the brazing sheet may be etched using an acidic aqueous solution or an alkaline aqueous solution after intermediate annealing or final annealing, if necessary. By carrying out the etching, the oxide film formed by the heating in intermediate annealing or final annealing can be weakened or removed. As a result, the brazing property of the brazing sheet can be further improved. When etching the brazing material surface, if the brazing material is clad on one side of the core material, only the brazing material surface may be etched, or both the brazing material surface and the opposite side may be etched. If the brazing material is clad on both sides of the core material, both sides are etched.

[0084] Examples of the acidic solution used for etching the brazing sheet include aqueous solutions of sulfuric acid, hydrochloric acid, nitric acid, phosphoric acid, and hydrofluoric acid. These acids may be used alone or in combination of two or more. From the viewpoint of more efficiently removing the oxide film, it is preferable to use a mixed aqueous solution containing hydrofluoric acid and an acid other than hydrofluoric acid, and it is more preferable to use a mixed aqueous solution of hydrofluoric acid and sulfuric acid or a mixed aqueous solution of hydrofluoric acid and nitric acid. Examples of the alkaline solution used for etching the brazing sheet include aqueous solutions of sodium hydroxide, potassium hydroxide, calcium hydroxide, and the like. These alkaline solutions may be used alone or in combination of two or more. When etching is performed using an alkaline solution, it is preferable to perform desmutting using an aqueous sulfuric acid solution or an aqueous nitric acid solution after etching.

[0085] In the method for producing an aluminum alloy brazing sheet of the present invention, it is preferable to suppress the growth of an oxide film and the concentration of Mg, Li and Ca in the oxide film during the production process.

[0086] The aluminum alloy brazing sheet of the present invention is used for brazing in an inert gas atmosphere without using flux. When the aluminum alloy brazing sheet of the present invention is brazed in an inert gas atmosphere without using flux, oxide particles containing Mg, Li and Ca, whose volume change rate relative to the oxide film before the brazing heat is 0.990 or less, are formed on the surface, so that the newly formed surface of the brazing material is easily exposed, and the sheet exhibits excellent brazing properties.

[0087] The aluminum alloy sheet (A) of the present invention is an aluminum alloy sheet obtained by brazing the aluminum alloy brazing sheet of the present invention in an inert gas atmosphere without using a flux, and is an aluminum alloy sheet on which oxide particles containing Mg, Li, and Ca are formed, the volume change rate of which is 0.990 or less relative to the oxide of the aluminum alloy brazing sheet before brazing heating. The oxide containing Mg, Li, and Ca formed on the surface of the aluminum alloy sheet (A) of the present invention is particulate, and the volume change rate of which is 0.990 or less relative to the oxide of the aluminum alloy brazing sheet before brazing heating, so that a new surface of the aluminum alloy appears on a part of the brazing sheet surface during brazing heating. Examples of the inert gas include nitrogen gas and argon gas. During heating, the oxygen concentration in the furnace when the temperature of the brazing sheet is 400°C or higher is 100ppm or less, and the oxygen concentration when the temperature of the brazing sheet is 570°C or higher is 20ppm or less, preferably 10ppm or less.

[0088] The aluminum alloy sheet (A) of the present invention is an aluminum alloy sheet to which an aluminum alloy brazing sheet has been brazed. EXAMPLES

[0089] Examples of the present invention will be described below in comparison with comparative examples to demonstrate the effects of the present invention. Note that these examples are merely illustrative of one embodiment of the present invention, and the present invention is not limited thereto.

[0090] The core ingots and brazing filler ingots having the compositions shown in Tables 1 and 2 were cast by continuous casting, and the core ingots were machined to 163 mm long and 163 mm wide, the core ingots clad only with brazing filler material on one side were machined to a thickness of 27 mm, and the core ingots clad with brazing filler material on both sides were machined to a thickness of 24 mm. The brazing filler ingots were hot-rolled at 500°C to a thickness of 3 mm, cooled, and then cut to a size of 163 mm long and 163 mm wide.

[0091] [Table 1]

[0092] [Table 2]

[0093] The prepared brazing material ingots and core material ingots were stacked in the combination shown in Table 3, then hot rolling and cold rolling were performed, and final annealing was performed under the conditions shown in Table 4 to obtain a soft clad material, or hot rolling and cold rolling were performed, and then intermediate annealing was performed under the conditions shown in Table 4, and then cold rolling was performed to obtain a soft clad material, or hot rolling and cold rolling were performed, and then intermediate annealing was performed under the conditions shown in Table 4, and then cold rolling was performed, and then final annealing was performed under the conditions shown in Table 4 to obtain a soft clad material. In addition, in the cases shown in Table 4, cleaning was performed after annealing. The final plate thickness was 0.3 to 1.0 mm. The obtained clad plate material was used as a test material. The thickness of the oxide film on the brazing material surface of the test material was measured by XPS (X-ray photoelectron spectroscopy). Oxygen was analyzed by XPS in the depth direction from the material surface, and the position of the measured oxygen peak half-width was taken as the oxide film thickness. In addition, the molar ratios of Mg, Li, and Ca in terms of atoms relative to aluminum (the sum of metallic aluminum and aluminum components in aluminum oxide) within the oxide film thickness (e.g., Mg content / Al content) were calculated.

[0094] The oxide film thickness of 10 nm or less is most preferable as A, more than 10 nm and 50 nm or less as B, and more than 50 nm as C, and these are shown in the "Oxide film thickness" column of Table 4. In the "Molar ratio" column, 0.1 or less is A, more than 0.1 and 0.5 or less is B, and more than 0.5 is C.

[0095] The gap filling test allows the brazing property of each test material to be evaluated. The test pieces used in the gap filling test were assembled in a SUS jig with 3003 bare material on the vertical plate and the test material on the horizontal plate, as shown in Figure 1, and brazed in a furnace in a nitrogen gas atmosphere without using flux. The brazing conditions were as follows: oxygen concentration in the furnace was controlled to 50 ppm or less when the test piece temperature was 400°C or higher during heating, oxygen concentration was controlled to 10 ppm or less when the test piece temperature was 570°C or higher, and the test piece temperature was set to 600°C. The length of the vertical plate in the general gap filling test (LWS T8801) was 55 mm, but the length of the vertical plate in this test piece was 25 mm, and the gradient of the gap formed between the horizontal plate and the vertical plate was increased to simulate a heat exchanger with a large gap.

[0096] In the gap filling test, brazeability can be evaluated based on the length FL of the fillet formed after brazing. The "Brazeability" column in Table 3 lists the FL and soundness of the fillet, which are rated on a three-level scale: A if the fillet is 5 mm or more and there is no partial fillet break, B if the fillet is 5 mm or more and there is partial fillet break, and C if it is less than 5 mm, with A being determined to be the pass level.

[0097] The volume change rate of oxide particles containing Mg, Li, and Ca formed after brazing relative to the oxide film before brazing heat was calculated by dividing the molecular weight of the oxide by the density described in a publicly known document to determine the volume per oxygen atom, and then dividing this by the volume per oxygen atom of the oxide film before brazing heat. The volume per oxygen atom of the oxide film before brazing heat was calculated by dividing the volume per oxygen atom of the oxide film before brazing heat by the volume per oxygen atom of the film component Al. 2 O 3 and its density is 3.0 g / cm 3The analysis of the obtained clad plate material and the results of the brazeability performance test are shown in Table 3.

[0098] [Table 3]

[0099] [Table 4]

Claims

1. An aluminum alloy brazing sheet for use in brazing in an inert gas atmosphere without using flux, At least one side of the core material is clad with a brazing material; the core material is an aluminum alloy core material containing aluminum or one or more of 1.50 mass% or less Fe, 1.50 mass% or less Si, 2.00 mass% or less Cu, 2.00 mass% or less Mn, 3.00 mass% or less Zn, 0.30 mass% or less Cr, 0.30 mass% or less Ti, 0.30 mass% or less Zr, 0.10 mass% or less In, and 0.10 mass% or less Sn, with the remainder being aluminum and unavoidable impurities; the brazing filler metal is an aluminum alloy brazing filler metal containing 4.00 to 13.00 mass% Si, one or more of more than 0.03 mass% and not more than 3.00 mass% Mg, more than 0.03 mass% and not more than 3.00 mass% Li, and more than 0.03 mass% and not more than 3.00 mass% Ca, with the remainder being aluminum and unavoidable impurities; an aluminum alloy brazing sheet in which, by brazing heat, an oxide containing any one or more of Mg, Li and Ca is formed on the surface of the brazing material side, the volume change rate of which is 0.990 or less relative to a surface oxide film on the surface of the brazing material side before brazing heat; the atomic molar ratio of Mg, Li, and Ca to Al in the oxide formed on the surface of the brazing material of the aluminum alloy brazing sheet before brazing heating is 0.5 or less; An aluminum alloy brazing sheet characterized by:

2. 2. The aluminum alloy brazing sheet according to claim 1, wherein the aluminum alloy brazing sheet is a two-layer material in which the brazing material is clad on one side of the core material.

3. 2. The aluminum alloy brazing sheet according to claim 1, wherein the aluminum alloy brazing sheet is a three-layer material in which both sides of the core material are clad with the brazing material.

4. The aluminum alloy brazing sheet is a three-layer material in which one surface of the core material is clad with the brazing material and the other surface of the core material is clad with a skin material, The skin material is an aluminum alloy skin material containing aluminum or 6.00 mass% or less of Zn, with the remainder being aluminum and unavoidable impurities; 2. The aluminum alloy brazing sheet according to claim 1,

5. The aluminum alloy brazing sheet according to any one of claims 1 to 4, characterized in that the core material further contains one or more of 3.00 mass% or less of Mg, 3.00 mass% or less of Li, and 3.00 mass% or less of Ca.

6. The aluminum alloy brazing sheet according to any one of claims 1 to 5, characterized in that the core material further contains 1.00 mass% or less of Bi.

7. The aluminum alloy brazing sheet according to any one of claims 1 to 6, characterized in that the brazing material further contains 1.00 mass % or less of Bi.

8. The aluminum alloy brazing sheet according to any one of claims 1 to 7, characterized in that the brazing material further contains one or more of 0.05 mass% or less of Na, 0.05 mass% or less of Sr, 0.05 mass% or less of Sb, 8.00 mass% or less of Zn, 4.00 mass% or less of Cu, 1.00 mass% or less of Fe, 1.00 mass% or less of Mn, 0.30 mass% or less of Cr, 0.30 mass% or less of Ti, 0.30 mass% or less of Zr, 0.10 mass% or less of In, and 0.10 mass% or less of Sn.

9. The aluminum alloy brazing sheet according to claim 4, characterized in that the skin material further contains one or more of 2.00 mass% or less Mn, 3.00 mass% or less Mg, 5.00 mass% or less Si, 1.50 mass% or less Fe, 1.00 mass% or less Cu, 0.30 mass% or less Ti, 0.30 mass% or less Zr, 0.30 mass% or less Cr, 0.10 mass% or less In, and 0.10 mass% or less Sn.

10. 10. The aluminum alloy brazing sheet according to claim 1, wherein the thickness of an oxide formed on the surface of the brazing material of the aluminum alloy brazing sheet is 50 nm or less.

11. A method for producing an aluminum alloy brazing sheet, comprising at least hot working and cold working on (1) a laminate in which brazing filler ingot / core ingot are stacked in this order, (2) a laminate in which brazing filler ingot / core ingot / brazing filler ingot are stacked in this order, or (3) a laminate in which brazing filler ingot / core ingot / skin ingot are stacked in this order, to obtain an aluminum alloy brazing sheet, the core ingot is an aluminum alloy containing aluminum or one or more of 1.50 mass% or less Fe, 1.50 mass% or less Si, 2.00 mass% or less Cu, 2.00 mass% or less Mn, 3.00 mass% or less Zn, 0.30 mass% or less Cr, 0.30 mass% or less Ti, 0.30 mass% or less Zr, 0.10 mass% or less In, and 0.10 mass% or less Sn, with the remainder being aluminum and unavoidable impurities; The brazing filler metal ingot is an aluminum alloy containing 4.00 to 13.00 mass% Si, one or more of more than 0.03 mass% and not more than 3.00 mass% Mg, more than 0.03 mass% and not more than 3.00 mass% Li, and more than 0.03 mass% and not more than 3.00 mass% Ca, with the remainder being aluminum and unavoidable impurities; The ingot for skin material is aluminum or an aluminum alloy containing 6.00 mass% or less of Zn, with the remainder being aluminum and unavoidable impurities, Between passes of rolling in cold working, intermediate annealing is performed by heating at 250 to 450°C for 1 hour or more in an atmosphere controlled to have an oxygen concentration of 10,000 ppm or less and a dew point of 20°C or less, or after the last cold working pass, final annealing is performed by heating at 250 to 450°C for 1 hour or more in an atmosphere controlled to have an oxygen concentration of 10,000 ppm or less and a dew point of 20°C or less, or both between passes of rolling in cold working and after the last cold working pass, annealing is performed by heating at 250 to 450°C for 1 hour or more in an atmosphere controlled to have an oxygen concentration of 10,000 ppm or less and a dew point of 20°C or less; Due to an aluminum alloy brazing sheet in which, by brazing heat, an oxide containing any one or more of Mg, Li and Ca is formed on the surface of the brazing material side, the volume change rate of which is 0.990 or less relative to a surface oxide film on the surface of the brazing material side before brazing heat; The atomic molar ratio of Mg, Li and Ca to Al in the oxide formed on the surface of the brazing material of the aluminum alloy brazing sheet before brazing heating is 0.5 or less. A method for producing an aluminum alloy brazing sheet, comprising the steps of:

12. The method for producing an aluminum alloy brazing sheet according to claim 11, characterized in that the core ingot further contains one or more of 3.00 mass% or less Mg, 3.00 mass% or less Li, and 3.00 mass% or less Ca.

13. The method for producing an aluminum alloy brazing sheet according to claim 11 or 12, characterized in that either the core material ingot or the brazing material ingot further contains 1.00 mass % or less of Bi.

14. The method for producing an aluminum alloy brazing sheet according to any one of claims 11 to 13, characterized in that the brazing material ingot further contains any one or more of 0.05 mass% or less of Na, 0.05 mass% or less of Sr, 0.05 mass% or less of Sb, 8.00 mass% or less of Zn, 4.00 mass% or less of Cu, 1.00 mass% or less of Fe, 1.00 mass% or less of Mn, 0.30 mass% or less of Cr, 0.30 mass% or less of Ti, 0.30 mass% or less of Zr, 0.10 mass% or less of In, and 0.10 mass% or less of Sn.

15. The method for producing an aluminum alloy brazing sheet according to any one of claims 11 to 14, characterized in that the skin material ingot further contains any one or more of 2.00 mass% or less Mn, 3.00 mass% or less Mg, 5.00 mass% or less Si, 1.50 mass% or less Fe, 1.00 mass% or less Cu, 0.30 mass% or less Ti, 0.30 mass% or less Zr, 0.30 mass% or less Cr, 0.10 mass% or less In, and 0.10 mass% or less Sn.

16. The method for producing an aluminum alloy brazing sheet according to any one of claims 11 to 15, characterized in that the brazing material surface of the clad material is etched using either one or both of an acidic aqueous solution and an alkaline aqueous solution, or both of an acidic aqueous solution and an alkaline aqueous solution, after the intermediate annealing if intermediate annealing is performed, after final annealing if final annealing is performed, or after either or both of the intermediate annealing and final annealing if both intermediate annealing and final annealing are performed.

Citation Information

Patent Citations

  • Production of non-oxidizing gas atmosphere non-flux brazing material and brazing method

    JP1998180489A

  • Production of non-oxidation gas atmosphere fluxless brazing material and brazing method

    JP1999285817A

  • Method for brazing aluminum material

    JP2004358519A

  • Flux-less brazing method of aluminum material, brazing sheet for flux-less brazing and method for manufacturing the same, brazing structure

    JP2013215797A

  • Fluxless brazing method for aluminum material and method of manufacturing brazed structure

    JP2013220461A